Tanner Holbrook: capstone - Holbrook, Tanner, artist (Colorado State University. Libraries, 2023)
The artist's statement: My work tends to emphasize illustration, as I am majoring in graphic design and drawing, and like to utilize my skill sets from both disciplines whenever possible. I am a huge appreciator of hand drawn work, and almost always draw things on paper before transferring them to a digital context. I typically prefer to use bold lines, colors, typefaces, etc. in the work that I do, as I want the things that I make to stand out in visually crowded environments. My work is heavily influenced by the urban environment, as I spend quite a bit of time exploring it by myself to find places to skateboard. I am fascinated by the idea of my work existing within the urban environment, whether it be on a t-shirt, a wall, a sticker on a post, or just about anything else that could potentially be seen on a walk through an urban area. My practice usually gravitates towards the use of a Sharpie when sketching and generating ideas. I believe a tool without an eraser is more conducive to the flow of ideas, as it eliminates the possibility of getting too focused on fixing small mistakes that can be fixed at a later point in my process. Once I have an idea that I am happy with I take it into a digital context, where I can refine it into a finished product.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design